MULTIPLE COMPLICATED CYSTS AS A INCIDENTAL FINDING - CASE REPORT - Dineva, Stoyanka; Halachev, Nikolay; Pavlova, Adelina (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Renal cysts are a common finding in the kidneys. A cystic lesion in the kidney that deviates from the typical "simple" cyst appearance should be viewed with suspicion and may warrant further imaging to exclude other renal cystic lesions, particularly variants of renal carcinoma. Findings common to all "simple" renal cysts are well-marginated, thin walls with no enhancement of the cyst. Rarely, simple cysts are complicated with hemorrhage, infection, inflammation, or ischemia. In these cases, there is a host reparative response that includes inflammatory cells, granulation tissue, and neovascularity. CT remains the major method of imaging and characterizing cystic renal lesions.